2012
DOI: 10.1155/2012/968040
|View full text |Cite
|
Sign up to set email alerts
|

Targeting PPARγSignaling Cascade for the Prevention and Treatment of Prostate Cancer

Abstract: The peroxisome proliferator-activated receptor-gamma (PPARγ) is a member of the hormone-activated nuclear receptor superfamily. PPARγ can be activated by a diverse group of agents, such as endogenous polyunsaturated fatty acids, 15-deoxy-Δ12,14-prostaglandin J2 (15d-PGJ2), and thiazolidinedione (TZD) drugs. PPARγ induces antiproliferative, antiangiogenic, and prodifferentiation pathways in several tissue types, thus making it a highly useful target for downregulation of carcinogenesis. These TZD-derived novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 121 publications
0
50
0
Order By: Relevance
“…PPARG has been implicated in adipocyte differentiation, functioning as a critical link between lipid and carbohydrate metabolism (19). The role of PPARG1 (isoform 1) role in cancer biology is poorly characterized, with both tumor suppressing and oncogenic effects reported (20,21). PPARG2 (isoform 2) is expressed at negligible levels in murine tumors and human cell lines, at both the mRNA and protein levels (18).…”
Section: Discussionmentioning
confidence: 99%
“…PPARG has been implicated in adipocyte differentiation, functioning as a critical link between lipid and carbohydrate metabolism (19). The role of PPARG1 (isoform 1) role in cancer biology is poorly characterized, with both tumor suppressing and oncogenic effects reported (20,21). PPARG2 (isoform 2) is expressed at negligible levels in murine tumors and human cell lines, at both the mRNA and protein levels (18).…”
Section: Discussionmentioning
confidence: 99%
“…8,9) Studies suggest that PPARγ activation inhibits the proliferation of malignant cells from different lineages such as liposarcoma, breast adenocarcinoma, prostate carcinoma, colorectal carcinoma, non-small-cell lung carcinoma, pancreatic carcinoma, bladder cancer, and gastric carcinoma. 10) Nonsteroidal anti-inflammatory drugs (NSAIDs) reduce inflammation by decreasing the synthesis of prostaglandin (PG), and inhibiting NF-κB and PPARγ activation. [11][12][13] NSAIDs are one of the most widely used medicines for the prevention and/ or treatment of various diseases.…”
mentioning
confidence: 99%
“…3,14) Activation of PPARγ inhibits the production of inflammatory cytokines [4][5][6][7] and the proliferation of malignant cells. 10) NSAIDs reduce inflammation by activating PPARγ. [11][12][13] Therefore, it is thought that the PPARγ rs1801282 polymorphism influences cancer risk in conjunction with NSAID usage.…”
mentioning
confidence: 99%
“…PPARγ has been investigated as a therapeutic target for cancer treatment. Certain previous studies have reported that PPARγ is able to induce anti-proliferative, anti-angiogenic and pro-differentiation signaling pathways in specific tissue types, thus serving a role in the pathogenesis and progression of various types of cancer, including prostate cancer (24,25). Using TZDs as PPARγ ligands, previous studies have investigated the effect of PPARγ on the metastatic potential and investigated its underlying mechanisms (26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%